Improved HIV-1 specific T-cell responses by short-interval DNA tattooing as compared to intramuscular immunization in non-human primates - Verstrepen, B; Bins, A; Rollier, C; Mooij, P; Koopman, G; Sheppard, N; Sattentau, Q; Wagner, R; Wolf, H; Schumacher, T; Heeney, J; Haanen, J (2008)
The new intradermal DNA delivery technique, termed DNA tattooing might overcome the discrepancy between the encouraging immunogenicity results obtained with DNA vaccines in murine studies and the poor results obtained in non-human primates and humans, the so called "simian barrier". Here, we demonstrate a 10- to 100-fold increase in the magnitude of vaccine specific T-cell responses in peripheral blood from DNA tattooed rhesus macaques, as compared to T-cell responses in animals immunized via intramuscular (IM) route. A marked increase in the magnitude of the antigen specific T-cell responses as well as an increase in the number of animals responding to the immunogens was observed. These findings in non-human primates suggest that similar results may be observed in humans. Clinical trials are planned to validate tattooing as an optimal method of DNA vaccine delivery in humans. © 2008 Elsevier Ltd. All rights reserved.